'Centaurea akcadaghensis' and 'C. ermenekensis' (Asteracaeae), two new species from Turkey - Şirin, Emrah; Uysal, Tuna; Bozkurt, Meryem; Ertuğrul, Kuddisi (Mediterranean Botany, 2020)
Two new species of Centaurea subg. Cyanus (Asteraceae) from Anatolia are described and illustrated. Centaurea akcadaghensis Uysal & Şirin occurs on open Quercus forest of Levent Canyon (Akçadağ-Malatya) and differs from C. matthiolifolia Boiss. mainly in stem, leaves, central flowers and achenes measures. Centaurea ermenekensis Şirin & Uysal is restricted to steppes of Göktepe (Ermenek-Karaman) and can be distinguished from C. reuteriana Boiss. by the stem, number of capitula, involucre and median appendages measures.